2007
DOI: 10.1002/app.25871
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of iPP: Influence of operating conditions and molecular parameters

Abstract: An analysis of the crystallization kinetics of different grades of isotactic polypropylene (iPP) is here presented. To describe the crystallization kinetics as a function of molecular and operating parameters, the methodological path followed was the preparation of quenched samples of known cooling histories, calorimetric crystallization isotherms tests, differential scanning calorimetry cooling ramps, wide angle X-ray diffraction (WAXD) measurements, and density determination. The WAXD analysis performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The increase in ethylene content therefore improves the optical properties of the films before sterilization by reducing haze. However it also increases the difference in the optical properties of the films with sterilization and encourages secondary crystallization; this increased 'quenchability' of PP grades with reduced regularity due to stereodefects and/or comonomer incorporation has already been demonstrated before by La Carrubba et al [30]. After sterilization, the DSC analysis of the films reveals a double melting peak as already evidenced in Figure 1.…”
Section: Resultssupporting
confidence: 65%
“…The increase in ethylene content therefore improves the optical properties of the films before sterilization by reducing haze. However it also increases the difference in the optical properties of the films with sterilization and encourages secondary crystallization; this increased 'quenchability' of PP grades with reduced regularity due to stereodefects and/or comonomer incorporation has already been demonstrated before by La Carrubba et al [30]. After sterilization, the DSC analysis of the films reveals a double melting peak as already evidenced in Figure 1.…”
Section: Resultssupporting
confidence: 65%
“…Differential fast scanning calorimetry studies showed that this transition occurs at cooling rates between 200-500 C s À1 [41]. The transition depends on the material characteristics such as molecular weight and molecular weight distribution, but an exact correlation has not yet been found [42]. When a polymer melt gets into contact with the cold wall of the mold in compression molding or injection molding, the material in close contact to the wall cools very rapidly, which can be investigated by using non-isothermal crystallization experiments in differential fast scanning calorimetry [43].…”
Section: Introductionmentioning
confidence: 99%
“…For ZN‐iPP, great attention had been paid on the relationship between the average isotacticities and the crystallization behavior. Some researchers believed that the isotacticity has an important influence on the spherulitic morphology of iPP,15 it also strongly affects the crystallization characteristics,16, 17 for instance, the number of crystal nuclei at the initial stage, crystallization dynamics, the morphology, size, and perfection of crystals in the final product, and can even induce variations in the nucleation mechanism and the fold surface free energy and the work of chain folding of iPP 10, 18. However, some other researchers held different point of view 19, 20.…”
Section: Introductionmentioning
confidence: 99%